ADDITIONS TO THE MYXOBIOTA OF THE CENTRAL JUNGLE OF PERU: NEW RECORDS AND FIRST REPORT OF Craterium roseum (PHYSARALES, MYXOMYCETES, AMOEBOZOA) - MUÑUICO, Jhon Wilson (2023)
The Myxomycetes are a group of amoeboid protists involved on the decomposition of organic matter of plant origin. In Peru, around 22% of the species known worldwide have been recorded, but the territory is studied unevenly, and the Amazon tropical forests, and particularly the central jungle, has barely been explored. In the present work, the result of expeditions carried out in 2020 to the jungle of Pasco, Oxapampa province, is provided. Six species unknown in this territory are reported, and the species Craterium roseum is recorded for the first time to Peru. The species richness and diversity of this territory is underestimated and need of more exhaustive studies to have a precise idea about its myxobiota.